PEMBUATAN ABSTRAK PRODUK HUKUM PERATURAN WALIKOTA TAHUN 2015 DI JDIH SEKRETARIAT DPRD KOTA BANDUNG - Muhammad Rafa Pradipta; Iyep Saefulrahman; Selvi Centia (LPPM Universitas Abdurrab, 2025)
The provision of abstracts in legal products is an essential element in supporting public information transparency, as it serves as a summary of the rationale, legal basis, and content of the regulation. However, in the Legal Documentation and Information Network (JDIH) of the Secretariat of the Bandung City Regional House of Representatives, many legal products, particularly Mayor Regulations issued in 2015, are not yet accompanied by abstracts. This condition indicates that the management of legal documentation has not been optimized in accordance with the provisions of the Minister of Law and Human Rights Regulation No. 8 of 2019. This study aims to describe the implementation of abstract preparation by the JDIH unit, identify its supporting and inhibiting factors, and formulate efforts for optimization. A qualitative descriptive method was employed through observation, interviews, and literature review. The findings show that although abstract preparation refers to technical guidelines, limitations in human resources, facilities, and work systems remain the main obstacles. Supporting factors include clear regulations and adequate competence of legal personnel. In conclusion, strengthening internal policies, enhancing human resource capacity, improving infrastructure, and integrating digital systems are necessary to ensure that the provision of abstracts for legal products is carried out consistently, accountably, and in support of open legal information services to the public.